Commutative Energetic Subsets of BCK-Algebras - Jun, Young Bae; Roh, Eun Hwan; Song, Seok Zun (Bulletin of the Section of Logic, 2016)
The notions of a C-energetic subset and (anti) permeable C-value in BCK-algebras are introduced, and related properties are investigated. Conditions for an element t in [0, 1] to be an (anti) permeable C-value are provided. Also conditions for a subset to be a C-energetic subset are discussed. We decompose BCK-algebra by a partition which consists of a C-energetic subset and a commutative ideal.